SPIRITUALITY AND HEALING: PERCEPTIONS AND IMPLICATIONS ON THE AKAN OF GHANA - Opoku, John Kwaku (Advances in Social Sciences Research Journal, 2018)
Spirituality, over the years, has become an important concept, though complex. It has served as a means to providing meaning to life through feelings of hope and faith, as well as capable of promoting the well-being of the individual. Healing, on the other hand, implies a complete state of well-being. The paper assesses the perceptions and impact of the relationship between spirituality and healing on the Akan as a people. Using the mixed method approach, the study gives an extensive interpretation of the effects and influence of spirituality and healing on the Akan. It re-introduces the significance of spiritual systems on health and healing, and provides more information on better ways to holistically care for the sick. It suggests a constant observation and recognition of the dimensions of spirituality when considering population health.